Cross-section programs in Handball I and II: An experience in the development of the competences of the Dominican school curriculum (Original) (Revista científica Olimpia, 2020)
The research is supported by the most up-to-date knowledge, which runs on the sphere of action of the Physical Education professional. In the universe of knowledge everything is subject to change, an example of this is the "National Pact for Educational Reform of the Dominican Republic (2014-2030), signed on April 2, 2014 (Economic and Social Council, 2014 ), where it is stated that the teacher must not only fulfill his role in the classroom or school, but he must also continue (developing) his competences as situations arise, to influence society and the family. The investigation is being carried out in the Eugenio Campus María de Hostos, Higher Institute of Teacher Training “Salomé Ureña.” There was a population of 41 students, who are in the 3rd (ninth term) and 4 to (tenth term) year of the Degree in Physical Education, in Handball I and II Basically, research consists of an experience, to develop the contents of the subject through a didactic intervention, which uses transversal contents of four programs, language (mother tongue and English), scientific training - technical and biopsychosocial foundations of physical activity, sports and society. With the completion of this work, it is expected to contribute to the training of professionals of the highest ethical, communicative, creative, critical level, with personal and spiritual development, that affects the care of the physical, natural and psychological environment, in order to be transformative of a better citizen life project.
Keywords: cross-section programs; handball and skills development